Effect of different tillage methods on percolation loss in rice fields - MINI P. K; Prof. T. P. George (Guide) (Tavanur 1993 Kelappaji College of Agricultural Engineering and Technology)
Effect of different tillage methods on percolation loss in rice fields
Effect of different tillage methods on percolation loss in rice fields